Evaluasi Berkelanjutan Ekowisata Pesisir di Padepokan Ciliwung Condet - Pradini, Gagih; Kusumaningrum, Anisa Putri; Saleh, Muhammad Surya; Ardani, Putri Aulia; Gunadi, I Made Adhi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Tourism development occurs as part of the growing community's economic growth and is a planned and structured activity. Directions, policies, strategies, and programs for tourism development must be in line with and synergistic with the direction of national tourism development policies so as not to deviate from the goals of tourism development. Tourism development must follow the principles of sustainability, which combine ecological, social, and economic sustainability. This strategic approach to sustainable tourism is recommended for small-scale local management and benefits the whole community. As well as benefiting local communities, ecotourism has a direct contribution to conservation efforts. Starting from the planning, implementation, monitoring and evaluation stages, integrated management is needed that can integrate the interests of all stakeholders.